P-007 Poor Collaterals on Pre-treatment CT Angiography Predicts Poor Outcome After Successful Recanalization in Patients with Anterior Circulation Emergent Large Vessel Occlusion. (29th July 2016) - Goyal, N; Iftikhar, S; Tsivgoulis, G; Khorchid, Y; Choudhri, A; Hoit, D; Alexandrov, A; Arthur, A; Elijovich, L
Abstract : Background and purpose: The best imaging selection technique for endovascular treatment (EVT) remains a topic of debate. Collateral scores (CS) on pre-treatment CT angiography (CTA) have been associated with favorable outcome. We hypothesized that low CS on pre-treatment CTA may predict a poor outcome after EVT in successfully recanalised patients with emergent large vessel occlusions (ELVO). Methods: A retrospective chart review was performed for the University of Tennessee Health Sciences Center Acute Ischemic Stroke Database evaluating AIS patients presenting with CTA confirmed anterior circulation ELVO in a tertiary stroke center during a 3 year period. Only patients with successful recanalization (TICI 2 b or 3) after EVT were included in the analysis. A blinded neuroradiologist calculated the CTA CS and final infarct volume (FIV). Poor outcome after EVT was defined as symptomatic intracranial hemorrhage (SICH), cerebral edema requiring hypertonic treatment for ≥48 hours, hemicraniectomy, higher FIV, and poor clinical outcome of modified ranking scale (mRS)-score 3–6 at 3 months. Results: 58 AIS patients with anterior circulation ELVO (mean age 63 ± 13 years, 48% male, median admission NIHSS-score: 17 points, IQR 14–21) had successful recanalization after EVT. Systemic thrombolysis was administered in 38 patients (65.5%). A total of 31 patients (53%) achieved favorable outcome (FO). There was no significant difference in rates of hemicraniectomy (p = 1.000) and SICH (p = 0.667) after EVT when compared to patients with low and good CS. Patients with low CS tended to have higher rates of cerebral edema requiring hypertonic treatment (30% vs 13%, p = 0.340) after EVT. Patients with low CS had greater FIV (111 ± 71 vs 41 ± 66 cm 3, p = 0.007) and higher rates of poor clinical outcome (82% vs 39%, p = 0.017) in comparison to patients with high CS. A low CS was independently associated with poor clinical outcome (p = 0.048) in multiple logistic regression models adjusting for demographics, vascular risk factors, pretreatment SBP, admission NIHSS, intravenous thrombolysis, and onset to revascularization time. Conclusion: Low CS on pre-treatment CTA was correlated with significantly worse outcome despite successful recanalization as evident by higher FIV and higher rates of poor clinical outcome. Poor CS should be considered an important variable in futures trials comparing the medical versus interventional management of patients with ELVO. Disclosures: N. Goyal: None. S. Iftikhar: None. G. Tsivgoulis: None. Y. Khorchid: None. A. Choudhri: None. D. Hoit: None. A. Alexandrov: None. A. Arthur: None. L. Elijovich: None.